At the Intersection of Gender and Language: Why do Francophone Women have Lower Levels of Political Participation?. Issue 1 (2nd January 2016) - Beauregard, Katrine
ABSTRACT: In Canada, research has found few differences in levels of political participation between Francophones and Anglophones despite traditional differences in resources leading to participation. This study argues that it is when gender is considered alongside language that differences emerge. Differences in conditions between Francophone and Anglophone women may mean that the explanations for the gender gaps differ. Findings show that Francophone women in Québec have lower levels of political participation than Anglophone women and men across Canada. These gender gaps are small but significant. Differences in resources and involvement in voluntary associations help account for Québec Francophone women's lower participation. Additionally, these results indicate that the different political context and the different political influence of the women's movement in Québec matter in determining explanations for gender gaps in political participation.